Pemberdayaan Masyarakat Melalui Hilirisasi Umbi Ganyong Menjadi Anyong Cookies di Desa Bumi Pajo - Nursani; Khas Sukma Mulya; Muhammad Akbar; Rizky Ameliya; Muhammad Rizkan; Fajrin Hardinandar; Syafruddin (Sarau Institute, 2026)
Bumi Pajo Village, Donggo Sub-district, Bima Regency, is the main producing area of canna (Canna edulis), locally known as kalo dana, yet most of the harvest is still sold as fresh tubers at low prices due to limited processing knowledge and business management skills. This community service program aimed to downstream canna tubers into a value-added food product,